Basic Models for the Development of Inclusive Education in Moscow - M. R. Husnutdinova (Russian State Vocational Pedagogical University, 2018)
Introduction. The implementation of inclusive education in the Russian comprehensive schools is a multidimensional process followed by a complex of organisational and methodological problems. The participants of this process have expressed diverging views on the following ideas: what sequence it has to be implemented; who has to become a leading actor implementing new educational principles into practice; what main structural changes of the developed system in general education have to be in connection with the introduction of inclusive education. It is necessary to analyse and understand the existing disagreements between all participants of a process. Undoubtedly, the experts of inclusive education, who are directly engaged in its theory and practice, can give the most exact answers to arising acute issues. Their experience and skill level allow a picture of situation to be presented in the most objective way.The aim of the research was to analyse main models of a current stage and prospects in development of inclusive education inMoscow and throughoutRussia.Methodology and research methods. The research was based on the methodology of scenario approach. In June 2015, the Laboratory of Monitoring Studies at the Moscow State University of Psychology & Education implemented the research "Prospects for the development of inclusive education in Moscow" in the form of expert scenario-prognostic monitoring (method of ESMM). In the course of the survey, 81 experts (practitioners, scientists, representatives of educational organisations and the public, managers) were interviewed. The quantitative way of representing the estimates by respondents allowed formal and mathematical methods to be used when processing the results - the factorial and correlation types of analysis using the IBM SPSS Statistics software package.Results and scientific novelty. The vast majority of representatives of expert community were quite pessimistic about the situation on the introduction of inclusive concept of education in Moscow. Concerning the most relevant issues, professional and psychological unreadiness of personnel structure of educational institutions to perform labour duties in the new conditions of training and education for younger generation was ranked as a prevailing idea. Moreover, among other issues, the author noted insufficient number of inclusive schools in Moscow, absence of pedagogical support for children with disabilities, as well as special educational conditions, including programmes for social adaptation.Based on the distribution of peer reviews, three main models of developing inclusive education systems were revealed and described: state, social and educational. When organising and supporting a joint form of education for children with different needs inRussia, the priority is given to state structures in the first (state) model; in the second (social) - to public organisations. The third (educational) model is focused on gradual transition, in which the former rehabilitative educational establishments should be maintained by forging productive collaboration with comprehensive schools.Practical significance. Clearly defined experts' standpoints in relation to the current stage of developing inclusive education allow us to better understand ongoing processes. In addition, the knowledge of characteristics of each of them contributes to forecasting its possible development and adopting more effective management decisions.